Effect of different riser heights on sprinkler irrigation performance under constant operating pressure - Kuti, I. A.; Ewemoje, T. A.; Adabembe, B. A.; Musa, J. J.; Nwosu, S. C. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2020)
The study assessed the effect of different riser heights on the sprinkler irrigation performance to cater for the cultivation of taller crops and reduce water losses. A layout of 144 m2 was designed according to the length of mainline and lateral lines, and 36 catch cans were positioned in a grid of 2 m apart. The water caught in Cans were subjected to One-way ANOVA using the Tukey method in Minitab 17 Environment. The risers 4m, 3m and 2m, were significantly different because the means without any letter in common and concluded that some of the riser height have the different mean value of water caught in the catch cans. The results showed that as the riser height increased the mean application rate decreased. Also, the Coefficient of Uniformity (%) for riser height 2 m and 3 m were rated excellent. The Distribution of Uniformity (%) for 2 m and 3 m were rated excellent and fair. The study concluded that riser heights 2 m and 3 m had the optimum CU and DU at 1.6 bar (operating pressure) reduce water losses. The study suggested that sprinkler irrigation should be carried out in Gidan Kwano campus between 5:06 pm and 11:35 am. Also, wind direction should be established before the installation of sprinkler irrigation.